2012
DOI: 10.1007/s10750-012-1275-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of UV radiation on respiration, ammonia excretion, and survival of copepods with different feeding habits

Abstract: Solar ultraviolet radiation (UVR) is known to harm aquatic organisms by damaging key molecules. Here, we showed that UV-A as well as UV-B affected differentially the respiration, ammonia excretion, and mortality of the copepods Pseudodiaptomus marinus (herbivorous) and Labidocera bipinnata (omnivorous). Adding UV-A (320-400 nm, 62.4 W m -2 ) to PAR (400-700 nm, 278 W m -2 ) decreased respiration by 10.2% in P. marinus and 46.1% in L. bipinnata, and additionally, the presence of UV-B (280-320 nm, 2.63 W m -2 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In the present study, low pH was generally associated with low salinity, and it is not possible to disentangle the effects of pH and salinity on the respiration rates. Physiological conditions, age, biomass, UV radiations and food conditions could also play an important role in respiration rate (Ma et al 2013). In order to mitigate the effect of physiological and food conditions, only ovigerous females were considered, and they were starved shortly before the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, low pH was generally associated with low salinity, and it is not possible to disentangle the effects of pH and salinity on the respiration rates. Physiological conditions, age, biomass, UV radiations and food conditions could also play an important role in respiration rate (Ma et al 2013). In order to mitigate the effect of physiological and food conditions, only ovigerous females were considered, and they were starved shortly before the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated that crustaceans, a dominant component of zooplankton communities, are highly vulnerable to UV-B radiation [6] . Previous studies on planktonic (often neustonic) crustacean zooplankton showed that exposure to UV-B lead to behavioral [13] and physiological responses [14] [16] ultimately affecting a range of fitness components [17] conducive to increased mortality [18] [20] . Impacts of UV-B radiation is expected to be highest in tropical oligotrophic marine regions [11] , where high incident UV-B radiation combines with deep penetration to yield high UV-B doses to organisms inhabiting the mixed layer.…”
Section: Introductionmentioning
confidence: 99%